Mobilizing the Digital Opinion Movement #OraSudiSumbangIKN on Twitter - Anbarini, Ratih; Adi Wibowo, S. Kunto; Asri Sjarifah, Nuryah; Abdullah, Aceng (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
This study examines the role of #OraSudiSumbangIKN in shaping digital opinion support mobilization movements, measuring the effectiveness of digital networks, actors, and opinions on social media. The hashtag #OraSudiSumbangIKN emerged after the government's plan to form a crowdfunding scheme from the community to construct the National Capital City (Ibu Kota Negara/IKN) Nusantara. Using social media network (SMNA) analysis and Digital Opinion Movement theory, this study examines how these hashtags mobilize the digital opinion support of social media users. The study included 10,000 tweets on Twitter that were taken and analyzed using the Netlytic and Gephi web. The study found that conversations on #OraSudiSumbangIKN hashtags were not dominated by dominant actors. This finding confirms that the hashtag meets the Digital Movement of Opinion (DMO) characteristics, which are spontaneous and not organized by social media users. This hashtag also has other DMO characteristics, which are short-lived, and comments are homogeneous. In addition, the high number of tweets on hashtags can also be explained because they have a strong narrative and emotional side. This research has implications for the selection of interesting narratives and hashtags that need to be considered by social media activists or individuals to be able to create opinion mobilization on social media. In addition, the findings can be an illustration for the government and academics or experts in the field of public policy in determining the next policy so as not to provoke negative public opinion.